دور ممارسات إدارة التغيير في تحسين الإبداع التنظيمي بالمؤسسة الجزائرية دراسة حالة مؤسسة سونلغاز - بياض, مصطفى (جامعة الوادي - University of Eloued, 2023)
This paper is studying of the impact of change management in the Algerian institution on improving organizational creativity, a case study of Sonelgaz institution in the state of Tindouf. The questionnaire method was used to determine the effect between the two variables under study by distributing 105 questionnaires to a random sample of the study population. The study concluded that Sonelgaz institution in the state of Tindouf adopted the change management method, which contributed to improving the levels of organizational creativity in the institution under study
The role of change management’s practices in improving organizational creativity in the Algerian institution. A case study ofSonelgazinstitution.
مقال
Keywords: إدارة التغيير؛ الابداع التنظيمي؛ المؤسسة الجزائرية؛ مؤسسة سونلغاز؛; Change Management, Organizational Creativity, Algerian Institution, Sonelgaz Institution.